Carbon Stock Dynamics with Spatial and Temporal Approaches in Forest Area with Special Purpose (KHDTK) Senaru - Kertalam, Lalu Rizki Aji; Latifah, Sitti; Idris, Muhamad Husni (Jurnal Biologi Tropis, 2025)
Forests have the ability to reduce carbon dioxide (CO2) and store it in the form of biomass. This study aims to determine the dynamics of carbon stocks in the Senaru Special Purpose Forest Area (KHDTK) with a spatial and time approach. Data collection was carried out in July-August 2024. Located in Senaru KHDTK. Vegetation data collection was carried out by systematic sampling with random start, vegetation data taken in the form of species, diameter and height were carried out on 43 sample plots measuring 20x20m with sub plots of 10x10m, 5x5m and 2x2m.  Standing carbon stocks were determined using the allometric equation. Carbon stock dynamics were analyzed by comparing the results of the study with stock data from previous studies. Spatial analysis was conducted using ArcGis application with Inverse Distance Weight (IDW), Kriging and Spline spatial interpolation methods. The results showed that the average surface carbon stock was 66.35 tons/ha. It decreased by 13.48 tons/ha in 5 years, and decreased by 17.36 tons/ha in 10 years. The spatial interpolation method that has the least error rate is the Kriging method. To increase the carbon stock of Senaru KHDTK, it is necessary to increase the population of forestry plants including large-trunked multipurpose plants such as durian, dao, jackfruit and others.